Bilateral acute macular neuroretinopathy following influenza A infection - Charles W. Ryan; Rajesh C. Rao (IDCases)
A previously healthy 18-year-old female presented with bilateral cecocentral scotomas two-days after onset of confirmed Influenza A infection, consistent with a post-viral acute macular neuroretinopathy (AMN). Fundoscopy revealed bilateral small petaloid lightening in the nasal macula, and optical coherence tomography revealed thinning of the interdigitation zone, ellipsoid zone, and outer nuclear layer bilaterally. Scotomas and associated imaging findings showed partial improvement in the weeks following diagnosis. This case demonstrates that AMN may be triggered Influenza A infection, and that resulting scotomas and retinal thinning may improve in the weeks following the initial insult.